FINANCIAL APPLICATION OF PALM PLASMA IN OIL PALM PLANTATIONS IN INDONESIA BY-LAW NUMBER 11 OF 2020 - Manik, April Tiodora (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
Law Number 11 of 2020 Article 29 contains business licensing for cultivation starting from land use areas, forest area release areas, facilitation of the development of surrounding community gardens covering an area of 20% of the land area, along with reporting to the central government and regional governments. However, compliance with this regulation remains inconsistent, and there is limited empirical research assessing the extent to which companies adhere to this requirement. Moreover, the relationship between financial reporting and the implementation of palm oil plasma has not been extensively explored. This study discusses how oil palm plantation companies in Indonesia have appropriately implemented Law Number 11 of 2020, especially in community plantation development facilities of 20%, known as palm oil plasma, and its relationship with financial reporting. This study uses a sample of seven plantation companies in Indonesia with a scale from 2019 to 2023. The study method uses quantitative study techniques. This study examines the application of palm plasma in oil palm plantations in Indonesia by Law Number 11 of 2020. The independent variable refers to Indonesia by Law Number 11 of 2020, while the dependent variable refers to the application of palm plasma in oil palm plantations. Based on the results of statistical tests, it can be concluded that seven oil palm plantation companies in Indonesia have not been able to implement Law Number 11 of 2020, as they have not properly applied the palm plasma system. This may be due to financial constraints, lack of infrastructure, or limited support from stakeholders. Additionally, challenges such as unclear regulatory guidelines, difficulties in land acquisition, and weak coordination between companies and smallholder farmers may have contributed to the ineffective implementation.